The Steel Prince - Schwab, Victoria (Schwab, Victoria. Shades of magic (Graphic novel), 2019)
The thrilling, epic tale of the young and arrogant prince Maxim Maresh, long before he became the king of Red London and adoptive father to Kell, the lead of A Darker Shade of Magic! The youthful Maresh is sent to a violent and unmanageable port city on the Blood Coast of Verose, on strict orders from his father, King Nokil Maresh, to cut his military teeth in this lawless landscape. There, he encounters an unruly band of soldiers, a lawless landscape, and the intoxicatingly deadly presence of the newly returned pirate queen, Arisa... Collects Shades of Magic: The Steel Prince #1-4.